2009
DOI: 10.4095/226712
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Alteration Study of the VMS-hosting Paleoproterozoic Bear Lake volcanic suite, Flin Flon Belt, Northern Manitoba

Abstract: The Bear Lake suite of the Paleoproterozoic Flin Flon Arc Assemblage consists of a large basaltic andesite shield volcano crowned by a caldera containing effusive to volcaniclastic rhyolite to andesite flows and a thick pelitic unit, the latter which hosts the White Lake and Cuprus volcanogenic massive sulphide deposits (VMS). The Bear Lake suite is also host to an extensive zone of epidote-enriched synvolcanic hydrothermal alteration over 11 km by 3 km in dimension. This alteration zone is similar in size to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This flow involved the drawdown of cold seawater and convection and heating of this seawater in the volcanic rock pile to produce hydrothermal fluid that vented at the sea floor. Several studies have demonstrated that the deeper parts of these regional alteration zones have been leached of metal and, in some cases, sulfur, with mass-balance calculations indicating that the amount of metals leached exceeds the metal present in known deposits (Gibson et al, 1983;Brauhart et al, 2001;Huston et al, 2001;Galley et al, 2009;Jowitt et al, 2009).…”
Section: Sources Of Ore Fluids Metals and Sulfurmentioning
confidence: 99%
“…This flow involved the drawdown of cold seawater and convection and heating of this seawater in the volcanic rock pile to produce hydrothermal fluid that vented at the sea floor. Several studies have demonstrated that the deeper parts of these regional alteration zones have been leached of metal and, in some cases, sulfur, with mass-balance calculations indicating that the amount of metals leached exceeds the metal present in known deposits (Gibson et al, 1983;Brauhart et al, 2001;Huston et al, 2001;Galley et al, 2009;Jowitt et al, 2009).…”
Section: Sources Of Ore Fluids Metals and Sulfurmentioning
confidence: 99%